Oriented carbon fiber filled organic silicon composite material as well as preparation method and application thereof

By introducing phytic acid and iron tetraoxide on the surface of the carbon fiber and induced the orientation of the carbon fiber by using magnetic fields, the problems of deforming ability of existing thermally conductive interface materials under high filling amounts are solved, and the efficient thermal conductivity of high-efficiency under low filling amounts are achieved.

CN119899534AActive Publication Date: 2025-04-29ZHENGZHOU UNIV

Patent Information

Application Number
CN202510129534.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-29
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The existing thermal conductivity of the thermal conductivity of the existing thermal interface materials is improved under high filling amount but the deformation ability is reduced. The random distribution leads to interface thermal resistance and phonon scattering, making it difficult to form an efficient thermal conductivity path.

Method used

By introducing phytic acid and iron tetraoxide, the surface of the carbon fiber is modified, and the magnetic field is used to induce the orientation of the carbon fiber in the silicone matrix to form a directional thermal conduction path.

Benefits of technology

It significantly improves thermal conductivity at low fill amounts, maintains the flexibility and mechanical properties of the composite material, and reduces interface thermal resistance and phonon scattering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899534A_ABST
    Figure CN119899534A_ABST
Patent Text Reader

Abstract

The invention discloses an oriented carbon fiber filled organic silicon composite material and a preparation method and application thereof, and belongs to the technical field of polymer-based heat conduction interface materials.The preparation method includes the steps that carbon fibers are subjected to surface treatment and oxidation treatment to obtain oxidized carbon fibers; adding the oxidized carbon fiber and phytic acid into water to obtain phytic acid modified carbon fiber; adding the phytic acid modified carbon fiber into water, adding ferric chloride and ferrous sulfate, fixing iron ions on the surface of the phytic acid modified carbon fiber, and adding sodium hydroxide to obtain phytic acid-ferroferric oxide modified carbon fiber; the preparation method comprises the following steps: mixing vinyl silicone oil, hydrogen-containing silicone oil and a catalyst, adding the phytic acid-ferroferric oxide modified carbon fibers, homogenizing and defoaming, arranging the phytic acid-ferroferric oxide modified carbon fibers in an external magnetic field in an oriented orientation manner along the direction of the magnetic field, and curing to obtain the oriented carbon fiber filled organic silicon composite material. The phytic acid and the ferroferric oxide are introduced, so that the carbon fiber still has excellent heat-conducting property under the condition of low filling amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer-based thermal conductive interface materials, and more specifically to an oriented carbon fiber filled organic silicon composite material and a preparation method and application thereof. Background Art

[0002] With the increasing power density of modern micro-devices, microprocessors, LEDs and other electronic products, heat dissipation methods and heat dissipation efficiency have attracted more and more attention. With the continuous increase in chip power, minimizing the thermal resistance of the device and improving the heat dissipation efficiency are of great significance to ensure the high performance and stability of microelectronic devices. Thermal conductive interface materials are used to connect two different materials in the entire heat flow path, which can effectively improve the heat conduction between the two solid interfaces, improve the thermal management level of electronic components, and play a key role in the field of thermal packaging. Thermal conductive interface materials are usually composite materials formed by taking polymer materials as the matrix and filling a certain amount of thermal conductive fillers. Generally speaking, thermal conductive fillers mainly include three types of metals, ceramics and carbon materials, while polymer matrix materials are usually mostly silicone, rubber and resin materials.

[0003] The polymer matrix material mainly affects the preparation process and mechanical properties of the thermal interface material, while the thermal conductive filler is the main factor that determines the thermal conductivity of the thermal interface material. Generally speaking, by filling the polymer matrix with thermal conductive fillers of appropriate particle size and filling amount to reach the percolation threshold of the thermal interface material, a relatively complete thermal conductive path can be formed between the polymer matrix and the thermal conductive filler, thereby greatly improving the thermal conductivity of the thermal interface material. This method of directly adding thermal conductive fillers to the polymer matrix does not involve complex physical processes and chemical reactions, and the overall process is safe and simple. However, in order to obtain thermal conductive interface materials with ideal thermal conductivity, researchers mainly improve the thermal conductivity of polymer-based composite materials by adding thermal conductive fillers such as copper, aluminum, aluminum oxide, boron nitride, graphene, etc. to silicone and epoxy resin polymer matrix materials, and disperse inorganic thermal conductive fillers in the polymer matrix through simple physical blending, thereby obtaining polymer-based thermal conductive composite materials with certain thermal conductivity and mechanical properties. However, adding a high amount of thermal conductive fillers to the polymer matrix will reduce the deformation capacity of the thermal interface material and make the thermal conductive composite material prone to cracking. In addition, the random distribution of high-filling thermal conductive fillers in the polymer matrix will aggravate the phonon scattering and interface thermal resistance in the composite material, making it difficult to form an efficient thermal conduction path, which is not conducive to improving the thermal conductivity of the composite material. Summary of the invention

[0004] In view of the above problems, the present invention provides an oriented carbon fiber filled silicone composite material and a preparation method thereof. The oriented carbon fiber filled silicone composite material prepared by the present invention introduces phytic acid and ferrosoferric oxide, so that the carbon fiber still has excellent thermal conductivity under low filling amount.

[0005] The first object of the present invention is to provide a method for preparing an oriented carbon fiber filled with organic silicon composite material, comprising the following steps: in an organic solvent, surface treating the carbon fiber to remove organic impurities, and then performing oxidation treatment to obtain oxidized carbon fiber. Oxidized carbon fiber and phytic acid are added to water, and a complexation reaction occurs at 30°C to 50°C to obtain phytic acid modified carbon fiber; phytic acid modified carbon fiber is added to water, and ferric chloride and ferrous sulfate are added at 50°C to 70°C, and the iron ions are fixed on the surface of phytic acid modified carbon fiber by chelation of phytic acid and iron ions, and sodium hydroxide is added to cause a coprecipitation reaction to obtain phytic acid-ferroferric oxide modified carbon fiber; for example, the reaction temperature of the complexation reaction is 30°C, 35°C, 40°C, 45°C, 50°C, etc. The temperature for adding ferric chloride and ferrous sulfate is 50°C, 55°C, 60°C, 65°C, 70°C, etc., but is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0006] After the vinyl silicone oil, hydrogen-containing silicone oil and catalyst are evenly mixed, phytic acid-ferroferric oxide modified carbon fiber is added, and after homogenization and degassing treatment, the phytic acid-ferroferric oxide modified carbon fiber is oriented and arranged along the direction of the magnetic field in an external magnetic field, and then cured to obtain an oriented carbon fiber filled silicone composite material.

[0007] In the preparation process of the present invention, the carbon fiber is first surface treated to remove organic impurities remaining on the surface of the carbon fiber during the preparation process of the carbon fiber, and then an oxidation treatment is performed to obtain an oxidized carbon fiber, and phytic acid is introduced on the surface of the oxidized carbon fiber. Phytic acid is a phosphorus-containing organic acid with multiple phosphate groups, which enables it to react with the surface of the oxidized carbon fiber to obtain a phytic acid-modified carbon fiber; then, the phytic acid-modified carbon fiber is used as a raw material, and the iron ions are fixed to the surface of the carbon fiber by the chelation of phytic acid to metal ions, and then sodium hydroxide is added, and the magnetic ferroferric oxide nanoparticles are deposited on the surface of the asphalt-based carbon fiber by the coprecipitation reaction of the iron ions. Phytic acid-ferroferric oxide modified carbon fiber is obtained; then, under the drive of an external magnetic field, the phytic acid-ferroferric oxide modified carbon fiber is oriented in the organosilicon composite material to obtain an oriented carbon fiber filled organosilicon composite material. The carbon fiber used in the present invention is an asphalt-based carbon fiber, and the asphalt-based carbon fiber has excellent thermal conductivity.

[0008] In a preferred embodiment of the present invention, the ratio of oxidized carbon fiber to phytic acid is 1g:7mg~8mg, and the reaction time of the complexation reaction is 24h~48h. For example, the ratio of oxidized carbon fiber to phytic acid is 1g:7mg, 1g:7.5mg, 1g:8mg, etc., and the reaction time of the complexation reaction is 24h, 30h, 36h, 42h, 48h, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0009] In a preferred embodiment of the present invention, the mass ratio of phytic acid modified carbon fiber and ferric chloride is 10:3~4.5; for example, the mass ratio of phytic acid modified carbon fiber and ferric chloride is 10:3, 10:3.5, 10:4, 10:4.5, etc.; the mass ratio of phytic acid modified carbon fiber and ferrous sulfate is 10:1.5~4; for example, the mass ratio of phytic acid modified carbon fiber and ferrous sulfate is 10:1, 10:2, 10:3, 10:4, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0010] In a preferred embodiment of the present invention, the mass ratio of phytic acid modified carbon fiber to sodium hydroxide is 1:0.2-0.5. For example, the mass ratio of phytic acid modified carbon fiber to sodium hydroxide is 1:0.2, 1:0.3, 1:0.4, 1:0.5, etc.; the reaction time of the coprecipitation reaction is 1h-3h, for example, the reaction time of the coprecipitation reaction is 1h, 2h, 3h, etc., but is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0011] In a preferred embodiment of the present invention, the mass ratio of vinyl silicone oil to hydrogen-containing silicone oil is 100:2.5-4; for example, the mass ratio of vinyl silicone oil to hydrogen-containing silicone oil is 100:2.5, 100:3, 100:3.5, 100:4, etc.; the mass ratio of vinyl silicone oil to catalyst is 100:0.3-0.7, for example, the mass ratio of vinyl silicone oil to catalyst is 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0012] In a preferred embodiment of the present invention, the addition amount of phytic acid-ferroferric oxide modified carbon fiber is 10% to 20% of the total mass of vinyl silicone oil and hydrogen-containing silicone oil. For example, the addition amount of phytic acid-ferroferric oxide modified carbon fiber is 10%, 12%, 14%, 16%, 18%, 20% of the total mass of vinyl silicone oil and hydrogen-containing silicone oil, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0013] In a preferred embodiment of the present invention, the time of the external magnetic field is 1h~1.5h. For example, the time of the external magnetic field is 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, the surface treatment is treated at 40°C to 60°C for 10h to 14h; for example, the surface treatment temperature is 40°C, 50°C, 60°C, etc., and the treatment time is 10h, 11h, 12h, 13h, 14h, etc. The oxidation treatment is a solution of nitric acid and sulfuric acid, and the treatment is carried out at 40°C to 60°C for 4-6h, for example. The oxidation treatment temperature is 40°C, 50°C, 60°C, etc., and the treatment time is 4h, 4.5h, 5h, 5.5h, 6h, etc., but is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0015] The second object of the present invention is to provide an oriented carbon fiber filled organic silicon composite material prepared by the above preparation method.

[0016] The third object of the present invention is to provide the use of the above-mentioned oriented carbon fiber filled organic silicon composite material in the preparation of thermal conductive materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, phytic acid is first grafted onto the surface of asphalt-based carbon fiber through the complexation of phytic acid, and then the magnetic ferroferric oxide nanoparticles are deposited onto the surface of asphalt-based carbon fiber by the chelation of phytic acid to metal ions and the coprecipitation reaction of iron ions. Phytic acid as a linker can enhance the binding force between magnetic ferroferric oxide nanoparticles and asphalt-based carbon fiber, and improve the stability of magnetic ferroferric oxide nanoparticles on the surface of asphalt-based carbon fiber. The asphalt-based carbon fiber modified by phytic acid and magnetic ferroferric oxide nanoparticles has magnetic responsiveness, and the modified asphalt-based carbon fiber is induced to be vertically oriented in the organosilicon matrix under the action of an external magnetic field, and an oriented carbon fiber filled organosilicon thermal conductive composite material is prepared at a low thermal conductive filler filling amount. The orientation direction of the carbon fiber in the organosilicon thermal conductive composite material is consistent with the phonon transmission direction, forming an effective heat conduction path, and greatly improving the thermal conductivity of the organosilicon composite material. The present invention can make the asphalt-based carbon fiber oriented in the organosilicon matrix, forming an efficient heat conduction path, so as to obtain a high-performance thermal conductive composite material at a low filling amount, and maintain the good flexibility and mechanical properties of the organosilicon composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a preparation flow chart of the present invention.

[0019] Figure 2This is the hysteresis loop of the phytic acid-ferroferric oxide modified carbon fiber sample prepared in Example 2.

[0020] Figure 3 These are optical photographs of the phytic acid-ferroferric oxide modified carbon fiber sample prepared in Example 2 dispersed in water under conditions without a magnetic field and with a magnetic field, wherein a is an optical photograph of the phytic acid-ferroferric oxide modified carbon fiber sample under conditions without a magnetic field, and b is an optical photograph of the phytic acid-ferroferric oxide modified carbon fiber sample under conditions with a magnetic field.

[0021] Figure 4 Thermal conductivity diagram of different materials.

[0022] Figure 5 These are thermal images of different materials, where a is a thermal image and b is a time and temperature curve of different materials.

[0023] Figure 6 A graph showing the tensile strength of different materials.

[0024] Figure 7 Graph of elastic modulus for different materials.

[0025] Figure 8 The elongation at break diagram for different materials.

[0026] Fig. 9 This is a diagram of the Shore hardness of different materials.

[0027] Fig.10 Volume resistivity diagram of different materials. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Modern electronic products are developing rapidly in the direction of miniaturization, integration and lightweight, and thermal management has become a key technical challenge. Developing thermal interface materials with high thermal conductivity is an effective strategy for electronic products to achieve efficient thermal management. Polymers are widely used as the matrix of thermal interface materials because of their light weight, easy processing, low cost and stable physical and chemical properties. Carbon fiber itself has high thermal conductivity, low cost, easy modification, and can effectively improve the thermal conductivity of polymer-based composites. However, simple physical mixing between polymers and carbon fibers often leads to more phonon scattering, which is not conducive to improving the thermal conductivity of composites. Moreover, carbon fiber usually needs to be filled in a higher amount to improve the thermal conductivity of the composite material, but too high a filling amount of carbon fiber will reduce the flexibility and mechanical properties of the composite material. Therefore, how to make the thermally conductive filler form a good thermal conductive path at a low filling amount, thereby improving the thermal conductivity of the composite material, has become the key to the development of high-performance thermal interface materials. Based on this, the present invention provides a method for preparing an oriented carbon fiber filled silicone composite material, and the preparation flow chart is shown as follows. Figure 1 As shown in the figure, phytic acid acts as a connector between asphalt-based carbon fibers and magnetic ferroferric oxide nanoparticles. Phytic acid can be modified to the surface of asphalt-based carbon fibers through complexation, and can also make the magnetic ferroferric oxide nanoparticles more stably bonded to the surface of carbon fibers through chelation of metal ions, thereby enhancing the binding force between the magnetic ferroferric oxide nanoparticles and asphalt-based carbon fibers, which is conducive to better inducing the directional orientation of carbon fibers in the organic silicon matrix under the action of an external magnetic field. Phytic acid mainly provides binding sites for the deposition of magnetic ferroferric oxide nanoparticles on asphalt-based carbon fibers, plays a fixing role on them, and is conducive to improving the uniform distribution of magnetic ferroferric oxide nanoparticles on the surface of carbon fibers, avoiding the agglomeration of magnetic ferroferric oxide nanoparticles, thereby reducing the thermal resistance between thermal conductive fillers and improving the thermal conductivity of the composite material.

[0030] The vinyl silicone oil used in the present invention is RH-Vi1323, the hydrogen-containing silicone oil is RH-H536, the size of the asphalt-based carbon fiber is 160-200 μm, the diameter is 7-10 μm, and the manufacturer is Japan Deyan Carbon Fiber Co., Ltd.

[0031] Example 1 (1) Disperse 5g of asphalt-based carbon fiber in 60mL of acetone, react under normal pressure at 40℃ for 14 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 8g of asphalt-based carbon fiber to 50mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 60℃ for 8 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0032] (2) 5 g of the oxidized carbon fiber obtained in step (1) and 40 mg of phytic acid are completely dispersed in 100 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 24 h in a constant temperature water bath at 50 ° C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50 ° C for vacuum drying for 12 hours to obtain phytic acid modified carbon fiber.

[0033] (3) Weigh 3 g of the dried phytic acid modified carbon fiber and completely disperse it in 40 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 70 °C, add 1.08 g of ferric chloride hexahydrate and 0.56 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 30 minutes, and then quickly add 0.8 g of sodium hydroxide to the mixed solution to make the iron ions coprecipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 1 hour, stop the reaction, let the reaction product stand for 1 hour, separate the reaction product by magnetic means, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0034] (4) After 80 g of vinyl silicone oil, 2 g of hydrogenated silicone oil and 0.3 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 10 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 3 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 15 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1 hour, and finally cured in a 1000°C vacuum drying oven for 3 hours to obtain an oriented carbon fiber filled silicone composite material.

[0035] Example 2 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0036] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0037] (3) Weigh 4 g of the dried phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of carbon fiber and water to 60 °C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions coprecipitate and deposit on the surface of the asphalt-based carbon fiber. Continue the reaction for 2 hours and then stop the reaction. After standing for 2 hours, separate the reaction products by magnetism, filter under reduced pressure, and dry to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0038] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 15 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 25 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1.5 hours, and finally cured in a 120°C vacuum drying oven for 2 hours to obtain an oriented carbon fiber filled silicone composite material.

[0039] Example 3 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0040] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0041] (3) Weigh 4 g of the dried phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of carbon fiber and water to 60 °C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions coprecipitate and deposit on the surface of the asphalt-based carbon fiber. Continue the reaction for 2 hours and then stop the reaction. After standing for 2 hours, separate the reaction products by magnetism, filter under reduced pressure, and dry to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0042] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 10 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 25 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1.5 hours, and finally cured in a 120°C vacuum drying oven for 2 hours to obtain an oriented carbon fiber filled silicone composite material.

[0043] Example 4 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0044] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0045] (3) Weigh 4 g of the dried phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of carbon fiber and water to 60 °C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions coprecipitate and deposit on the surface of the asphalt-based carbon fiber. Continue the reaction for 2 hours and then stop the reaction. After standing for 2 hours, separate the reaction products by magnetism, filter under reduced pressure, and dry to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0046] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 20 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 25 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1.5 hours, and finally cured in a 120°C vacuum drying oven for 2 hours to obtain an oriented carbon fiber filled silicone composite material.

[0047] Example 5 (1) Disperse 20g of asphalt-based carbon fiber in 100mL of acetone, react at 60℃ and normal pressure for 10 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 10g of asphalt-based carbon fiber to 70mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 60℃ for 12 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0048] (2) 10 g of the oxidized carbon fiber obtained in step (1) and 80 mg of phytic acid are completely dispersed in 200 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are fully reacted for 48 h in a constant temperature water bath at 50° C. under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50° C. and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0049] (3) Weigh 5 g of the dried phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 70 ° C, add 2.16 g of ferric chloride hexahydrate and 1.68 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 60 minutes, and then quickly add 2.4 g of sodium hydroxide to the mixed solution to make the iron ions co-precipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 3 hours, stop the reaction, let the reaction product stand for 3 hours, separate the reaction product, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0050] (4) After 100 g of vinyl silicone oil, 4 g of hydrogenated silicone oil and 0.7 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 20 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 5 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a vacuum drying oven at 40°C for 30 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1.5 hours, and finally cured in a vacuum drying oven at 140°C for 1 hour to obtain an oriented carbon fiber filled silicone composite material.

[0051] Example 6 (1) Disperse 5g of asphalt-based carbon fiber in 60mL of acetone, react under normal pressure at 40℃ for 14 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 8g of asphalt-based carbon fiber to 50mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 60℃ for 8 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0052] (2) 5 g of the oxidized carbon fiber obtained in step (1) and 35 mg of phytic acid are completely dispersed in 100 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are fully reacted for 48 h in a constant temperature water bath at 30° C. under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50° C. and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0053] (3) Weigh 3 g of the dried phytic acid modified carbon fiber and completely disperse it in 40 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 70 °C, add 0.9 g of ferric chloride hexahydrate and 0.45 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 30 minutes, and then quickly add 0.8 g of sodium hydroxide to the mixed solution to make the iron ions coprecipitate and deposit on the surface of the asphalt-based carbon fiber. Continue the reaction for 2.5 hours and then stop the reaction. After standing for 1 hour, separate the reaction products by magnetism, filter under reduced pressure, and dry to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0054] (4) After 100 g of vinyl silicone oil, 2.5 g of hydrogenated silicone oil and 0.3 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 10 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 3 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 15 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1 hour, and finally cured in a 1000°C vacuum drying oven for 3 hours to obtain an oriented carbon fiber filled silicone composite material.

[0055] Example 7 (1) Disperse 5g of asphalt-based carbon fiber in 60mL of acetone, react under normal pressure at 40℃ for 14 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 8g of asphalt-based carbon fiber to 50mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 60℃ for 8 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0056] (2) 5 g of the oxidized carbon fiber obtained in step (1) and 40 mg of phytic acid are completely dispersed in 100 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 24 h in a constant temperature water bath at 50 ° C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50 ° C for vacuum drying for 12 hours to obtain phytic acid modified carbon fiber.

[0057] (3) Weigh 3 g of the dried phytic acid modified carbon fiber and completely disperse it in 40 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 70 ° C, add 1.35 g of ferric chloride hexahydrate and 1.2 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 30 minutes, and then quickly add 1.5 g of sodium hydroxide to the mixed solution to make the iron ions co-precipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 1 hour, stop the reaction, let the reaction product stand for 1 hour, separate the reaction product by magnetism, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0058] (4) After 80 g of vinyl silicone oil, 2 g of hydrogenated silicone oil and 0.3 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 15 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 3 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a 40°C vacuum drying oven for 15 minutes, and then the carbon fiber and silicone mixture are placed in an external magnetic field for 1 hour, and finally cured in a 1000°C vacuum drying oven for 3 hours to obtain an oriented carbon fiber filled silicone composite material.

[0059] Comparative Example 1 100 g of vinyl silicone oil, 4 g of hydrogenated silicone oil and 0.7 g of Karstedt catalyst were mixed evenly, and then stirred and homogenized at 12000 rpm for 5 minutes using a high-speed homogenizer, followed by degassing in a 40° C. vacuum drying oven for 30 minutes, and finally cured in a 140° C. vacuum drying oven for 1 hour to obtain a pure silicone material.

[0060] It should be noted that when the carbon fiber filling amount is 0, the unmodified carbon fiber filled silicone composite material, the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material are the same material, that is, pure silicone material.

[0061] Comparative Example 2 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0062] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0063] (3) Weigh 4 g of phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 60 ° C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions co-precipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 2 hours, stop the reaction, let the reaction product stand for 2 hours, separate the reaction product by magnetism, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0064] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 15 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain an unoriented carbon fiber filled silicone composite material.

[0065] Comparative Example 3 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0066] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0067] (3) Weigh 4 g of phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 60 ° C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions co-precipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 2 hours, stop the reaction, let the reaction product stand for 2 hours, separate the reaction product by magnetism, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0068] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 10 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain an unoriented carbon fiber filled silicone composite material.

[0069] Comparative Example 4 (1) Disperse 10g of asphalt-based carbon fiber in 80mL of acetone, react under reflux at 50℃ for 12 hours, filter the reaction product under reduced pressure and rinse with acetone, and dry it in a vacuum drying oven at 50℃ for 12 hours. After drying, add 9g of asphalt-based carbon fiber to 60mL of a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, react at 50℃ for 10 hours, dilute the reaction product with a large amount of deionized water, and filter it under reduced pressure. Wash it with a large amount of deionized water during filtration until the filtrate is neutral. After filtration, dry the asphalt-based carbon fiber in a vacuum drying oven at 50℃ for 12 hours to obtain oxidized carbon fiber for standby use.

[0070] (2) 8 g of the oxidized carbon fiber obtained in step (1) and 60 mg of phytic acid are completely dispersed in 150 mL of deionized water, and the phytic acid and the asphalt-based carbon fiber obtained in step (1) are allowed to fully react for 36 hours in a constant temperature water bath at 40°C under magnetic stirring. The reaction product is then subjected to reduced pressure filtration and rinsed with a large amount of deionized water. The reaction product is placed in a vacuum drying oven at 50°C and vacuum dried for 12 hours to obtain phytic acid-modified carbon fiber.

[0071] (3) Weigh 4 g of phytic acid modified carbon fiber and completely disperse it in 50 mL of deionized water. Then heat the mixture of phytic acid modified carbon fiber and water to 60 ° C, add 1.44 g of ferric chloride hexahydrate and 1.12 g of ferrous sulfate heptahydrate to the mixture, continue heating and stirring for 45 minutes, and then quickly add 1.6 g of sodium hydroxide to the mixed solution to make the iron ions co-precipitate and deposit on the surface of the asphalt-based carbon fiber. After continuing the reaction for 2 hours, stop the reaction, let the reaction product stand for 2 hours, separate the reaction product by magnetism, filter it under reduced pressure, and dry it to obtain asphalt-based carbon fiber modified with phytic acid and magnetic ferroferric oxide nanoparticles, which is recorded as phytic acid-ferroferric oxide modified carbon fiber and set aside.

[0072] (4) After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Karstedt catalyst are uniformly mixed, the phytic acid-ferroferric oxide modified carbon fiber obtained in step (3) is added according to 20 wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000 rpm for 4 minutes using a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture are degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain an unoriented carbon fiber filled silicone composite material.

[0073] Comparative Example 5 After 90g of vinyl silicone oil, 3g of hydrogenated silicone oil and 0.5g of Karstedt catalyst were evenly mixed, the original asphalt-based carbon fiber was added according to 15wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000rpm for 4 minutes with a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture was degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain a carbon fiber filled silicone composite material.

[0074] Comparative Example 6 After mixing 90g of vinyl silicone oil, 3g of hydrogenated silicone oil and 0.5g of Karstedt catalyst evenly, the original asphalt-based carbon fiber was added according to 10wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000rpm for 4 minutes with a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture was degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain an unoriented carbon fiber filled silicone composite material.

[0075] Comparative Example 7 After 90g of vinyl silicone oil, 3g of hydrogenated silicone oil and 0.5g of Karstedt catalyst were mixed evenly, the original asphalt-based carbon fiber was added according to 20wt% of the total mass of the vinyl silicone oil and the hydrogenated silicone oil, and stirred and homogenized at 12000rpm for 4 minutes with a high-speed homogenizer. Subsequently, the carbon fiber and silicone mixture was degassed in a vacuum drying oven at 40°C for 25 minutes, and then cured in a vacuum drying oven at 120°C for 2 hours to obtain an unoriented carbon fiber filled silicone composite material.

[0076] Magnetic properties test of phytic acid and magnetic ferroferric oxide nanoparticles co-modified carbon fiber: The magnetic properties of phytic acid and magnetic ferroferric oxide nanoparticles co-modified carbon fiber were tested by the American LakeShore 8600 magnetic measurement system. The modified carbon fiber samples were fully dried before testing and tested at room temperature. The test range was -20000 Oe~20000 Oe. The saturation magnetization of the modified carbon fiber was determined based on the hysteresis loop of the modified asphalt-based carbon fiber.

[0077] The magnetic response performance of the phytic acid-ferroferric oxide modified carbon fiber sample prepared in Example 2 was tested using a vibrating sample magnetometer. The hysteresis loop of the phytic acid-ferroferric oxide modified carbon fiber sample is shown in FIG. Figure 2 As shown. Phytic acid-ferroferric oxide modified carbon fiber has significant magnetic responsiveness. As the strength of the external test magnetic field changes, the magnetization intensity of the phytic acid-ferroferric oxide modified carbon fiber also changes. As the strength of the external magnetic field gradually increases, the magnetization intensity of the phytic acid-ferroferric oxide modified carbon fiber also increases. At the same time, the rate of increase of the magnetization intensity of the phytic acid-ferroferric oxide modified carbon fiber gradually slows down. Under a higher external magnetic field strength, the magnetization intensity of the phytic acid-ferroferric oxide modified carbon fiber gradually reaches saturation. The saturation magnetization intensity of the phytic acid-ferroferric oxide modified carbon fiber is 5.8 emu·g -1 , which has good ferromagnetic properties. This also proves that the magnetic ferroferric oxide nanoparticles have been successfully modified onto the surface of asphalt-based carbon fibers, and that there is a strong binding effect between the magnetic ferroferric oxide nanoparticles and the asphalt-based carbon fibers.

[0078] The phytic acid-ferroferric oxide modified carbon fiber prepared in Example 2 was uniformly dispersed in an aqueous solution. Optical photographs of the phytic acid-ferroferric oxide modified carbon fiber dispersed in an aqueous solution without and after applying an external magnetic field are shown in FIG. Figure 3 As shown. Figure 3 As shown in a in FIG. 1 , when no external magnetic field is applied, the phytic acid-ferroferric oxide modified carbon fiber can be uniformly dispersed in the water phase to form a uniform black mixture of phytic acid-ferroferric oxide modified carbon fiber and water, as shown in FIG. Figure 3 As shown in b, when an external magnetic field is applied, the phytic acid-ferroferric oxide modified carbon fiber can be attracted to one side of the magnet under the action of the magnetic field, resulting in a very obvious interface between the aggregated phytic acid-ferroferric oxide modified carbon fiber and water, which proves that the phytic acid-ferroferric oxide modified carbon fiber has good magnetic responsiveness, can respond to the external magnetic field and move in a directional manner under the action of the magnetic field. The good magnetic responsiveness of phytic acid-ferroferric oxide modified carbon fiber provides a basis for the preparation of asphalt-based carbon fiber / organic silicon composite thermal conductive materials with directional orientation of asphalt-based carbon fiber.

[0079] Thermal conductivity test of oriented carbon fiber filled silicone composites: The thermal conductivity of different samples was tested using the LongGwin9389 thermal resistance tester of Shanghai Longwin Company. First, the oriented carbon fiber filled silicone composite was prepared into square samples of 30 mm × 30 mm with thicknesses of 1 mm, 1.5 mm, and 2 mm, and the thermal resistance of samples of different thicknesses was measured, and the thermal conductivity of each sample was calculated based on the thermal resistance and thickness of the sample.

[0080] The thermal conductivity of the unoriented carbon fiber filled silicone composites prepared in Comparative Examples 2 to 4, the oriented carbon fiber filled silicone composites prepared in Examples 2 to 4, and the unmodified carbon fiber filled silicone composites prepared in Comparative Examples 5 to 7 at different carbon fiber filling amounts were tested using a thermal resistance tester. The experimental results are as follows: Figure 4 As shown. When the filling amount of carbon fiber gradually increases from 0 to 20wt%, the thermal conductivity of the unoriented carbon fiber filled silicone composite material and the unmodified carbon fiber filled silicone composite material shows a trend of gradually increasing, while the thermal conductivity of the oriented carbon fiber filled silicone composite material shows a trend of first increasing and then decreasing. At the same carbon fiber filling amount, the thermal conductivity of the oriented carbon fiber filled silicone composite material is much higher than that of the unoriented carbon fiber filled silicone composite material and the unmodified carbon fiber filled silicone composite material. This may be mainly due to two reasons. On the one hand, the phytic acid-ferroferric oxide modified carbon fiber can be better oriented under the action of the external magnetic field when the filling amount is appropriate, so that the orientation direction of the carbon fiber and the phonon transmission direction are consistent, thereby effectively improving the thermal conductivity of the silicone composite material; on the other hand, when the filling amount of the phytic acid-ferroferric oxide modified carbon fiber is too high, it will not only lead to a large amount of interfacial thermal resistance, but also increase the steric hindrance, inhibit the orientation of the carbon fiber in the silicone matrix, and reduce the thermal conductivity of the composite material to a certain extent. When the filling amount of phytic acid-ferroferric oxide modified carbon fiber is 15wt%, the thermal conductivity of the oriented carbon fiber filled silicone composite is 1.857 Wm -1 K -1 , which is 2.52 times the thermal conductivity of the unoriented carbon fiber filled silicone composite material at the same filling amount, 3.37 times the thermal conductivity of the pure silicone material without carbon fiber filling, and 2.22 times the thermal conductivity of the unmodified carbon fiber filled silicone composite material. This proves that the silicone composite material filled with oriented phytic acid-ferroferric oxide modified carbon fiber has a more complete thermal conduction pathway and higher thermal conductivity.

[0081] Thermal imaging test of oriented carbon fiber filled silicone composites: The thermal imaging analysis of different samples was performed using the American FLIR T540 infrared thermal imaging analyzer, and the thermal imaging images of different samples during the heating process were recorded. Different samples were prepared into block samples with a length of 20 mm, a width of 20 mm, and a height of 2 mm. After the samples were kept at a constant temperature at room temperature, the samples were transferred to the heating table for heating, and the heating temperature of the heating table was set to 60°C. During the heating and heating process of the samples on the heating table, the samples were photographed using an infrared thermal imager, with one photo taken every 5 seconds, and 10 photos taken for each sample. The heat transfer rate of the composite samples at different carbon fiber filling amounts was analyzed by combining the time and temperature curves of different samples with thermal imaging photos.

[0082] The heat transfer rate of the oriented carbon fiber filled with silicone composite material was analyzed by infrared thermal imaging analysis technology at different filling amounts of 0, 10wt%, 15wt% and 20wt% of the phytic acid-ferroferric oxide modified carbon fiber prepared in Comparative Example 1 and Examples 2 to 3. The thermal imaging pictures of the oriented carbon fiber filled with silicone composite material at different time points are as follows: Figure 5 As shown in a in the figure, the corresponding heating curves of each sample are as follows Figure 5As shown in b. From the infrared thermal imaging image, it can be seen that with the extension of heating time, the temperature of the oriented carbon fiber filled silicone composite material under different carbon fiber filling amounts gradually increases. Under the observation and recording of the infrared thermal imager, the color of each oriented carbon fiber filled silicone composite material sample gradually changes from dark blue purple to light golden yellow, and from the color of each composite material sample at different time points, the color change speed of the oriented carbon fiber filled silicone composite material samples at different carbon fiber filling amounts is also different, which intuitively reflects that the silicone composite materials filled with different phytic acid-iron tetroxide modified carbon fibers have different heat transfer capabilities. The stronger the heat transfer capacity of the oriented carbon fiber filled silicone composite material, the faster the color change of the composite material sample. It is worth noting that after 50s of heating, the color of the samples of the oriented carbon fiber filled silicone composite material filled with different phytic acid-iron tetroxide modified carbon fibers eventually tends to be golden yellow, and the color difference between the samples is not obvious. This may be due to the heat absorption and heat dissipation of each oriented carbon fiber filled silicone composite sample reaching thermal equilibrium, and the temperature of the composite material gradually tends to be stable. The heating curves of oriented carbon fiber filled silicone composites with different carbon fiber filling amounts also show similar results. The heating rates of the oriented carbon fiber filled silicone composite samples were fast in the first 20 seconds of heating, and then the samples of the composite materials gradually entered the plateau period, the heating rate slowed down, and the temperature of the oriented carbon fiber filled silicone composite samples finally stabilized. When the phytic acid-ferroferric oxide modified carbon fiber filling amount was 15wt% and 20wt%, the heating rate of the oriented carbon fiber filled silicone composite samples was significantly higher than that of the composite samples with other filling amounts, especially the oriented carbon fiber filled silicone composite sample with a filling amount of 15wt% entered the temperature plateau period the earliest. The heating rate and heat transfer capacity of the oriented carbon fiber filled silicone composites at different phytic acid-ferroferric oxide modified carbon fiber filling amounts were significantly different, which was mainly related to the filling amount and directional orientation of the phytic acid-ferroferric oxide modified carbon fiber in the silicone matrix. In the time interval of 0 to 20 s, the heating rate of the oriented carbon fiber filled with silicone composite material sample with phytic acid-ferroferric oxide modified carbon fiber filling amount of 15wt% is 1.41℃ / s, which is much higher than the heating rate of other composite material samples. This is mainly because the phytic acid-ferroferric oxide modified carbon fiber can be fully oriented in the silicone matrix at an appropriate filling amount, thereby forming an efficient heat transfer path, which is conducive to improving the heat transfer capacity of the oriented carbon fiber filled silicone composite material. The results of thermal imaging pictures and heating curve experiments show that the silicone composite material filled with oriented phytic acid-ferroferric oxide modified carbon fiber has a fast heating rate and high heat transfer efficiency. When used as a thermal conductive interface material, it is beneficial to improve the thermal management level of electronic equipment, electronic components, etc.

[0083] Mechanical properties test of different samples: The mechanical properties of different samples were tested by an electronic universal tensile testing machine. First, different samples were prepared into dumbbell-shaped specimens with a gauge length of 20 mm, an aspect ratio of 5:1, and a thickness of about 2 mm according to the national standard GB / T1040-2018. The thickness of the specimens was accurately measured by a vernier caliper before the test, and then the test was carried out at a tensile rate of 10 mm / min. Each sample was tested 5 times in parallel, and the tensile strength, elastic modulus, and elongation at break of the sample were characterized according to the average value of the test results.

[0084] The mechanical properties including tensile strength, elastic modulus and elongation at break of the unoriented carbon fiber filled silicone composite materials prepared in Comparative Examples 2 to Comparative Examples 4 and the oriented carbon fiber filled silicone composite materials prepared in Examples 2 to 4 at different carbon fiber filling amounts were tested and analyzed by an electronic universal tensile testing machine. The experimental results are shown in Figure 6-Figure 8As shown. From the overall mechanical properties of the composite material, the tensile strength, elastic modulus and elongation at break of the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material all show an increasing trend with the increase of the filling amount of phytic acid-ferroferric oxide modified carbon fiber. This is mainly because the phytic acid-ferroferric oxide modified carbon fiber can play a role in mechanical reinforcement in the silicone composite material, thereby improving the mechanical properties of the silicone composite material. At the same carbon fiber filling amount, the tensile strength, elastic modulus and elongation at break of the unoriented carbon fiber filled silicone composite material are higher than those of the corresponding oriented carbon fiber filled silicone composite material. This may be because the tensile test direction of the electronic universal testing machine is perpendicular to the orientation direction of the phytic acid-ferroferric oxide modified carbon fiber in the silicone composite material, which leads to the poor ability of the oriented carbon fiber filled silicone composite material to withstand fracture stress. When the filling amount of carbon fiber is 10wt%, the tensile strength of unoriented carbon fiber filled silicone composite material and oriented carbon fiber filled silicone composite material are 0.145 MPa and 0.130 MPa, respectively, the elastic modulus is 0.168 MPa and 0.133 MPa, respectively, and the elongation at break is 119.5% and 109.4%, respectively. With the increase of the content of phytic acid-ferroferric oxide modified carbon fiber, the tensile strength, elastic modulus and elongation at break of unoriented carbon fiber filled silicone composite material and oriented carbon fiber filled silicone composite material also increase. When the filling amount of phytic acid-ferroferric oxide modified carbon fiber is 15wt%, the tensile strength of unoriented carbon fiber filled silicone composite material and oriented carbon fiber filled silicone composite material are 0.158 MPa and 0.138 MPa, respectively, the elastic modulus is 0.176 MPa and 0.157 MPa, respectively, and the elongation at break is 131.2% and 118.6%, respectively. This shows that the directional orientation of phytic acid-ferroferric oxide modified carbon fibers in silicone composites will lead to the loss of some mechanical properties of the composites under the corresponding carbon fiber filling content, but the oriented carbon fiber filled silicone composites still have relatively high tensile strength, elastic modulus and elongation at break, which can meet the mechanical property requirements of thermal conductive composites.

[0085] Shore hardness test of different samples: The Shore hardness of different samples was measured by O-type rubber hardness tester of Taizhou AiCe Instrument Co., Ltd. During the test, the different samples to be tested were first placed on a solid horizontal surface, and the hardness tester was held vertically by hand so that the hardness tester pressure needle was at least 12 mm away from the edge of the sample, and the hardness tester pressure needle was vertically pressed into the sample to be tested. When the hardness tester pressure foot and the sample were in full contact, the hardness value was read within 1 second. Repeat the hardness test five times at different positions at least 6 mm apart from the test site and calculate the average value.

[0086] The Shore hardness of the unoriented carbon fiber filled silicone composite material prepared in Comparative Examples 2 to 4 and the oriented carbon fiber filled silicone composite material prepared in Examples 2 to 4 was measured by a Shore hardness tester. The Shore hardness test results of the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material at different carbon fiber filling amounts are as follows: Fig. 9 As shown. The Shore hardness of both the unoriented carbon fiber filled silicone composite and the oriented carbon fiber filled silicone composite increases with the increase of carbon fiber content, showing a similar change pattern to the tensile strength, elastic modulus and elongation at break of the two silicone composites. Under the same phytic acid-ferroferric oxide modified carbon fiber filling amount, the Shore hardness of the oriented carbon fiber filled silicone composite is much higher than that of the unoriented carbon fiber filled silicone composite. This is mainly because the phytic acid-ferroferric oxide modified carbon fiber is vertically oriented in the silicone composite. When the oriented carbon fiber filled silicone composite is subjected to external force, the vertically oriented phytic acid-ferroferric oxide modified carbon fiber can provide greater resistance in the direction of external force. When the carbon fiber filling amount is 10wt%, the Shore hardness of the unoriented carbon fiber filled silicone composite and the oriented carbon fiber filled silicone composite are 41.0 H00 and 50.4 H00, respectively. As the carbon fiber filling amount increases to 20wt%, the Shore hardness of the unoriented carbon fiber filled silicone composite and the oriented carbon fiber filled silicone composite are 48.0 H00 and 58.2 H00, respectively. At this time, the Shore hardness of the oriented carbon fiber filled silicone composite is 1.21 times that of the unoriented carbon fiber filled silicone composite. This proves that the silicone composite filled with phytic acid-ferroferric oxide modified carbon fiber has higher Shore hardness and pressure bearing capacity at the same carbon fiber filling amount.

[0087] Volume resistivity test of different samples: The resistance of different samples was measured using the IViumSTST.H electrochemical workstation of IVium Company of the Netherlands, and the volume resistivity of each sample was calculated. First, different samples were prepared into rectangular samples with a specification of 10 mm × 10 mm × 2 mm. During the test, the samples were placed between two sensors on the electrochemical workstation and tested using the transient DC impedance method. The test temperature was 25°C, and the volume resistivity of each sample was calculated based on the resistance value obtained from the test.

[0088] The volume resistivity of the unoriented carbon fiber filled silicone composites prepared in Comparative Example 2 to Comparative Example 4 and the oriented carbon fiber filled silicone composites prepared in Example 2 to Example 4 at different filling amounts of phytic acid-ferroferric oxide modified carbon fiber was tested using an electrochemical workstation. The experimental results are shown in FIG. Fig.10As shown. The volume resistivity of the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material shows an overall downward trend with the increase of the filling amount of phytic acid-ferric tetroxide modified carbon fiber. This is mainly because the carbon fiber itself has good conductivity, and the increase of the filling amount of carbon fiber in the silicone matrix is ​​conducive to the transmission of electrons. At the same phytic acid-ferric tetroxide modified carbon fiber filling amount, the volume resistivity of the oriented carbon fiber filled silicone composite material is slightly lower than that of the unoriented carbon fiber filled silicone composite material, which may be caused by the orientation of phytic acid-ferric tetroxide modified carbon fiber in the silicone matrix. In summary, the volume resistivity of the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material is at a relatively high level, which shows that although the filling of phytic acid-ferric tetroxide modified carbon fiber reduces the volume resistivity of the composite material, the unoriented carbon fiber filled silicone composite material and the oriented carbon fiber filled silicone composite material still have high electrical insulation. When the filling amount of phytic acid-ferric tetroxide modified carbon fiber is 15wt%, the volume resistivity of the oriented carbon fiber filled silicone composite material is 3.14 × 10 11 When the phytic acid-ferroferric oxide modified carbon fiber is filled with a higher amount, the volume resistivity of the oriented carbon fiber filled with silicone composite material can still meet the electrical insulation requirements of the thermal conductive interface material.

[0089] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0090] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an oriented carbon fiber filled organic silicon composite material, characterized in that: The following steps are involved: In an organic solvent, the carbon fiber is surface treated to remove organic impurities, and then oxidized to obtain oxidized carbon fiber; The oxidized carbon fiber and phytic acid are added into water to undergo a complexation reaction at 30°C to 50°C to obtain phytic acid-modified carbon fiber; The phytic acid modified carbon fiber is added into water, and ferric chloride and ferrous sulfate are added at 50°C to 70°C, and the iron ions are fixed on the surface of the phytic acid modified carbon fiber through the chelation of phytic acid and iron ions, and sodium hydroxide is added to cause a coprecipitation reaction to obtain phytic acid-ferroferric oxide modified carbon fiber; After the vinyl silicone oil, hydrogen-containing silicone oil and catalyst are evenly mixed, phytic acid-ferroferric oxide modified carbon fiber is added, and after homogenization and degassing treatment, the phytic acid-ferroferric oxide modified carbon fiber is oriented and arranged along the direction of the magnetic field in an external magnetic field, and then cured to obtain an oriented carbon fiber filled silicone composite material.

2. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The ratio of oxidized carbon fiber to phytic acid is 1g:7mg~8mg, and the reaction time of the complexation reaction is 24h~48h.

3. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The mass ratio of phytic acid modified carbon fiber to ferric chloride is 10:3~4.5; The mass ratio of phytic acid modified carbon fiber and ferrous sulfate is 10:1.5~4.

4. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The mass ratio of phytic acid modified carbon fiber and sodium hydroxide is 1:0.2~0.5; The reaction time of the coprecipitation reaction is 1h~3h.

5. The method for preparing an oriented carbon fiber filled organosilicon composite material according to claim 1, characterized in that: The mass ratio of vinyl silicone oil to hydrogen-containing silicone oil is 100:2.5~4; the mass ratio of vinyl silicone oil to catalyst is 100:0.3~0.

7.

6. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The addition amount of phytic acid-ferroferric oxide modified carbon fiber is 10%~20% of the total mass of vinyl silicone oil and hydrogen silicone oil.

7. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The time of applying the external magnetic field is 1h~1.5h.

8. The method for preparing an oriented carbon fiber filled organic silicon composite material according to claim 1, characterized in that: The surface treatment is at 40℃~60℃ for 10h~14h; The oxidation treatment uses nitric acid and sulfuric acid as solution and is carried out at 40℃~60℃ for 4-6h.

9. An oriented carbon fiber filled organosilicon composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the oriented carbon fiber filled organic silicon composite material according to claim 9 in preparing a thermal conductive material.

Citation Information

Patent Citations

  • Ferroferric oxide / polypyrrole composite material and preparation method thereof

    CN108976820A

  • Preparation method and application of non-metal modified carbon fibers

    CN110652978A

  • Carbon fiber based on biological matrix surface modification, preparation method and composite material

    CN114575151A

  • Nano-silver modified carbon fiber coated organic silicon heat-conducting composite material as well as preparation method and application thereof

    CN119286258A

  • Acrylonitrile-based copolymer for carbon fiber

    JP2012214657A

Cited By

  • Basalt fiber composite material with fiber directional distribution and preparation method thereof

    CN120842780A